Two new species of the genus Deuteraphorura Absolon, 1901 (Hexapoda, Collembola, Onychiuridae) from Georgian caves with remarks on the subterranean biodiversity of the Caucasus Mountains - Parimuchová, Andrea; Barjadze, Shalva; Maghradze, Eter; Kováč, Ľubomír (European Journal of Taxonomy, 2025)
Specimens of Deuteraphorura collected in 11 Georgian caves were analysed morphologically and molecularly based on the COI gene barcode region. Two molecular delimitation methods revealed four species (MOTUs); however, only two of them were distinguished morphologically and are described in this paper as new to science. Both new species, D. colchisi sp. nov. and D. kozmani sp. nov., belong to the group with a pseudocellus on the first thoracic tergum; the differential diagnosis table to this species group is provided. The potential of the Caucasus as a hotspot region of subterranean biodiversity and evolution centre of subterranean animals is discussed.